Assessing postgraduate outcomes of research-intensive nursing science PhD programs: Methods and metrics. - Stolldorf, Deonni P.; Schirle, Lori; Kleinpell, Ruth; Akard, Terrah Foster; Piano, Mariann R. (Nursing Outlook, 2022)
• A comprehensive program evaluation plan is a hallmark of research-focused doctoral programs. • Studies and reports of longitudinal program evaluation of graduates of research-focused nursing doctoral programs are limited. • Standardization of core metrics and/or questions and follow-up timeline and a shared data repository is needed. Across disciplines and within higher educational systems, assessing postgraduate outcomes is essential for evaluating doctoral programs, including research-intensive nursing science doctoral programs. However, there are limited reports regarding methods and metrics related to postgraduate longitudinal evaluation of research-focused nursing doctoral programs. The purpose of this paper is to summarize studies in the area of postgraduate outcome assessment and provide recommendations regarding outcome methods and metrics for evaluating the effectiveness of research-focused nursing doctoral programs. PubMed/Medline, CINHAL Complete, and Google Scholar databases were searched using key words including PhD program, doctoral program, longitudinal evaluation, evaluation, program evaluation, PhD alumni survey, education outcomes and PhD program outcomes. We excluded non-English and full-text articles that were not available for review. Based on a review of the literature, there are few reports on methods and questionnaires for postgraduate outcome assessment. There is a critical need to develop standardized core metrics/questions, longitudinal assessments, and a shared data repository. The latter will allow for comparisons across nursing doctoral programs. Robust standardized longitudinal assessment of nursing doctoral programs is a necessary step for comparison across programs and re-envisioning the nursing doctoral education of the future.